Locoregional radionuclide therapy of glioblastoma with [211At]At-PDA-FAPI - Huan Ma; Tianzhen Ye; Guofeng Qu; Yilin Qin; Jiali Liao; Yuanyou Yang; Wei Zhang; Ning Liu; Feize Li (Scientific Reports)
Abstract Glioblastoma is the most common and aggressive tumor of the central nervous system. Locoregional administration of therapeutic radiopharmaceuticals appears to be a promising modality for recurrent glioblastomas. In this study, fibroblast activation protein alpha (FAPα) targeting molecule fibroblast activation protein inhibitor-04 (FAPI-04) was conjugated to polydopamine (PDA) nanoparticles, and then, α-emitter astatine-211 was labeled onto the nanocomposite to form [211At]At-PDA-FAPI. In vitro, [211At]At-PDA-FAPI was able to significantly reduce the cell viability, induce DSB formation, arrest cell cycle at G2/M phase and promote cell apoptosis. Furthermore, [211At]At-PDA-FAPI exhibited effective tumor inhibition ability in U87MG xenografts. Mice received 0.56 MBq [211At]At-PDA-FAPI showed a reduced tumor volume of approximately 65% on the 9th day after injection, and the median survival in this group (48 days) was obviously improved compared with that in the saline group (18 days). Meanwhile, increased apoptosis was also observed in tumor sites after [211At]At-PDA-FAPI treatment. In addition, H&E analysis of major organs confirmed the biological safety of [211At]At-PDA-FAPI. This study provides an effective and promising strategy for locoregional treatment of glioblastoma.